Analysis and modeling of Stresses and Deflections Generated on the Reversible Moldboard plow Attached to the Angular Scraper Under various soil conditions - Haleem, Rateeb; Rajab, Adel (Indonesian Journal Publisher, 2025)
This study was conducted theoretically using the (Inventor) software, which relies on the finite element method to determine the values of both maximum stress, principal stress, and deflection for both the angular scraper and the moldboard plow under conditions similar to field conditions. The study was conducted in two stages: the first stage involved fixing the dimensions and measurements of the angular scraper and then manufacturing it. The second stage involved field evaluation of the performance efficiency of the locally manufactured reversible moldboard plow with the angular scraper, comparing it with the reversible moldboard plow without the angular scraper, and studying some field performance indicators through a practical experiment that included the following factors: the use of the reversible moldboard plow at two levels (with the locally manufactured angular scraper and without the angular scraper), soil condition at two levels (with weed soil and without weed soil), using a Randomized Complete Block Design (RCBD) with split-plot design, and the effect of these factors on the studied traits, which included stress, vertical deflection ratio, lateral deflection ratio, and performance efficiency. The results showed that the angular scraper recorded higher values for both maximum stress and principal stress, while the moldboard of plow recorded the highest value for deflection. Moreover, untilled soil condition significantly outperformed in providing higher values for performance efficiency, while tilled soil condition significantly outperformed in providing higher values for both vertical and lateral deflection ratios. As for the plow, the plow with the angular scraper significantly outperformed in recording higher values for performance efficiency, while the plow without the angular scraper significantly outperformed in recording higher values for both vertical and lateral deflection ratios.